Validation of an Italian questionnaire to assess sleep disorders: The Sleep Disorders Score Questionnaire (SDS-Q) - Sergio GARBARINO; Ottavia GUGLIELMI; Giovanni RALLO; Nicola MAGNAVITA (Journal of Health and Social Sciences)
Introduction: Many occupational factors disturb sleep. This can have significant consequences because sle- ep problems mediate the relationship between work stress and health disorders. The objective of this study is to validate the Sleep Disorders Score Questionnaire (SDS-Q), a questionnaire designed to measure sleep disorders and their consequences in workers. Methods: A cross-sectional study was carried out. Validity was analysed by exploratory factor analyses, and reliability by Cronbach’s alpha. Results: The study was conducted with 240 male police officers. Principal component analysis confirmed the existence of 3 subscales, regarding Insomnia symptoms, Excessive daytime sleepiness (EDS) and Ob- structive Sleep Apnoea (OSA). The Cronbach’s alpha values of the subscales Insomnia symptoms (IS), Sleepiness symptoms (SS) and Apnoea symptoms (AS) were acceptable. Discussion and Conclusions: The Insomnia, Sleepiness and Apnoea subscales of SDS-Q have demonstra- ted good psychometric properties in terms of reliability and validity. The SDS-Q is a valid and reliable tool for assessing workers’ sleep problems and disorders.